Intangible assets of multinational enterprises in Ireland and their impact on euro area activity - Malin Andersson; Nina Blatnik; Stephen Byrne; Lorenz Emter; Belén Gonzalez Pardo; Valerie Jarvis; Martin Schmitz; Nico Zorell; Christoph Zwick (European Central Bank (ECB), 2024)
The activities of multinational enterprises (MNEs) have become an increasingly important feature of the euro area economy, affecting output, trade and financial linkages. MNEs contribute to domestic output by maintaining large production facilities, offering high-paid jobs, bringing in new technologies and generating tax revenues. Following statistical changes implemented in 2015 to better capture the increasing importance of intangible investment, the economic impact of MNE activities has become much more evident in measures of intellectual property product (IPP) investment and external IPP trade flows. MNE activities, which often entail large and instantaneous transfers of IPP, are frequently highly volatile and can blur real-time assessment - and forecasting - of the business cycle, the current account and the capital stock in the euro area. Focusing on Ireland, given the strong prevalence of MNE activities in that economy and their importance for the euro area aggregate, this paper assesses the usefulness of the "modified" series for Irish nonconstruction investment and services imports. Using the modified series would provide a more accurate picture of the domestic dynamics of the Irish economy and enhance real-time assessment of the euro area business cycle, current account and capital stock. This paper brings insights into the unwinding of IPP shocks, which is a more straightforward exercise than seeking to anticipate the shocks themselves. The conclusions of this work underline the urgent need for more granular and internationally harmonised data on MNE activities to gain a clearer understanding of the dynamics of IPP operations and the implications for both short and long-term macroeconomic developments.
Keywords: E22; F23; F62; 330; Intangible capital; multinational firms; macroeconomic impact of globalisation